VD_FINDINFO Arrêt / 2024 / 826 vom 7. November 2024 - VD Tribunal cantonal (2024)
ÉVALUATION DE L'INVALIDITÉ, AA, ENQUÊTEEN GÉNÉRAL, ACTIVITÉ LUCRATIVE INDÉPENDANTE | 10 al. 1 LAA, 16 LAA, 18 al. 1 LAA, 19 LAA, 20 LAA, 16 LPGA, 6 LPGA, 8 LPGA, 30 OLAA